Law & ethics for medical careers - Judson, Karen (Glencoe/McGraw-Hill, 2002)
This 12-chapter text prepares students to understand the legal and ethical issues inherent to working in an ambulatory health care setting. It features pertinent legal cases, anecdotes, and sidebars related to health-related careers. Content has been updated and special attention has been paid to legislation affecting health care.